2022
DOI: 10.1007/s11325-022-02565-7
|View full text |Cite
|
Sign up to set email alerts
|

Yawning and airway physiology: a scoping review and novel hypothesis

Abstract: Background and purpose Yawning is a stereotypical complex muscular movement and is commonly executed by most vertebrates. In seconds, the entire airway is fully dilated and surrounding muscles are powerfully stretched, most prominently around the pharynx. To date, yawning has been rarely studied, and as of yet there is no consensus on its main function. Material and methods To investigate a mechanical airway function for yawning, a literature search was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…The functions of spontaneous are evaluated in the review. As previously shown, the circadian hypothesis demonstrates that yawning is a behavior that reflects the circadian rhythm, the oxygenation theory believes yawning is an anticipant of airway collapse, while the brain cooling hypothesis indicates yawning is contributed to decreasing the temperature of the brain [9]; [11]; [10]. However, they all have flaws and drawbacks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The functions of spontaneous are evaluated in the review. As previously shown, the circadian hypothesis demonstrates that yawning is a behavior that reflects the circadian rhythm, the oxygenation theory believes yawning is an anticipant of airway collapse, while the brain cooling hypothesis indicates yawning is contributed to decreasing the temperature of the brain [9]; [11]; [10]. However, they all have flaws and drawbacks.…”
Section: Discussionmentioning
confidence: 99%
“…Some scientists suggested that yawning is for longterm oxygenation. Specifically, yawning creates an enlarged airway by muscle repositioning in the upper airway to anticipate airway collapse [11].…”
Section: Airway or Respiration Hypothe-sismentioning
confidence: 99%
See 2 more Smart Citations
“…Such yawning responses may occur one minute after the injection of thiopental or propofol, with an occurrence rate of approximately 50% [58]. Upper-airway collapse during the induction of anesthesia coincides with increased yawning, while upper-airway muscle dilation and decreased yawning caused either by either teeth clenching or opioids administrations coincides with obstructive sleep apnea-like symptoms [59]. Yawning after tPBM administration mimics the yawning that is elicited by thiopental or propofol administration during induction of general anesthesia.…”
Section: Supporting Evidencementioning
confidence: 90%